Improving IPAS Learning Outcome using the Problem-Based Learning Model in Elementary School - Kause, Migdes Christianto; Sunbanu, Halani F.; Selan, Yefris A.; Maulana, Reza (Jurnal Pijar Mipa, 2025)
The low level of Mastery of Minimum Competencies among students is caused by students still experiencing difficulties in developing their critical thinking skills. In classroom learning, students still have difficulty understanding literacy and numeracy.  The aim of this research is to determine the increase in the ability to master minimum competencies in elementary school students using the Problem-Based Learning model. The method used in this research is quantitative research, with an experimental research design. The experimental method has several designs, one of which is the quasi-experimental method (quasi-experimental). The sample in this research was students at Cibadak Elementary School, Bogor.  The sampling technique used is non-random sampling, where the research sample is taken not at random. The research results show that there is an increase in students' mastery of minimum competencies by using the Problem-Based Learning model. This is shown by the calculated t value obtained being greater than the t table with the calculated T value of 2.46, while the T table value is 1.65; this result shows that there is an increase in the use of the PBL model in improving students' Minimum Competency Assessment (MCA) abilities. Meanwhile, the results of calculating the N-Gain value obtained a value of 0.73% in the high category. This is because the use of the Problem-Based Learning model can facilitate students to be actively involved in learning, so that students' understanding of literacy and numeracy questions can increase.